Kajian Mitigasi Bencana Erupsi Gunung Merapi di Kecamatan Cangkringan Kabupaten Sleman - Nur Isnainiati; Muchammad Mustam; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Disaster is a condition that causes casualties, damage, and loss. Indonesia is a country that has kind of a complex disaster, so that disaster management should using the paradigm of disaster risk reduction through mitigation programs. This research is a study of disaster mitigation eruption of Mount Merapi in Cangkringan, Sleman. This study aims to determine the implementation of structural and non-structural mitigation disaster eruption in Mount Merapi by the government.This study used a qualitative research, the method is descriptive. In the implementation of mitigation eruption of Mount Merapi in Sleman Regency Cangkringan Sub District, government appears to coordinate with relevant agencies and cooperate with the private/NGO. Many communities involved in mitigation activities that arise in public understanding of the disaster, besides the ease of accessing information makes the implementation of mitigation successfully.The results of this study indicating that the implementation of structural and non- structural mitigation is affected by the same factors. Factors that affecting the implementation of mitigation disaster eruption in Mount Merapi is coordination, community participation, cooperation between government and private / NGO, public initiatives, and information.